2017
DOI: 10.3349/ymj.2017.58.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Urapidil for Older Hypertensive Patients with Acute Heart Failure: A Multicenter Randomized Controlled Trial

Abstract: PurposeUrapidil is putatively effective for patients with hypertension and acute heart failure, although randomized controlled trials thereon are lacking. We investigated the efficacy and safety of intravenous urapidil relative to that of nitroglycerin in older patients with hypertension and heart failure in a randomized controlled trial.Materials and MethodsPatients (>60 y) with hypertension and heart failure were randomly assigned to receive intravenous urapidil (n=89) or nitroglycerin (n=91) for 7 days. Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…The levels of ALT and AST mainly reflected the function of the liver, and the creatinine levels demonstrated the renal function. Both studies provided data on the toxicity of the drugs and reached the same conclusion, namely, the two drugs were similar in terms of safety 23,24. However, through the integrated analysis of the data, we found that urapidil caused less damage to the liver and kidney functions than nitroglycerin.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The levels of ALT and AST mainly reflected the function of the liver, and the creatinine levels demonstrated the renal function. Both studies provided data on the toxicity of the drugs and reached the same conclusion, namely, the two drugs were similar in terms of safety 23,24. However, through the integrated analysis of the data, we found that urapidil caused less damage to the liver and kidney functions than nitroglycerin.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, we performed a sensitivity analysis of the data. When we deleted the Yang et al (2017) study,24 the differences in heterogeneity disappeared and the result was not changed (Figure 11).…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have reported that urapidil is used for the treatment of patients with SH and AHF. [2023] However, no systematic review has explored the efficacy and safety of urapidil for treating SH and AHF. Thus, this study will demonstrate that urapidil administration is as effective in patients with SH and AHF.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, urapidil has reported to treat patients with SH and AHF very well. [2023] However, there is still no systematic study to assess the efficacy and safety in patients with SH and AHF. Therefore, this study will firstly explore the efficacy and safety of urapidil for the management of SH and AHF.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a clinical syndrome characterized by impaired cardiac function due to various cardiovascular diseases and has a mortality of approximately 50%. [ 1 , 2 ] Although progress has been achieved in HF treatment in recent years, the 5-year mortality of patients with HF remains high. HF can be caused by diseases of the endocardium, myocardium, pericardium, heart valves, and vessels or by metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%